On the Precise Link between Energy and Information - Cameron Witkowski; Stephen Brown; Kevin Truong (Entropy, 2024)
We present a modified version of the Szilard engine, demonstrating that an explicit measurement procedure is entirely unnecessary for its operation. By considering our modified engine, we are able to provide a new interpretation of Landauer’s original argument for the cost of erasure. From this view, we demonstrate that a reset operation is strictly impossible in a dynamical system with only conservative forces. Then, we prove that approaching a reset yields an unavoidable instability at the reset point. Finally, we present an original proof of Landauer’s principle that is completely independent from the Second Law of thermodynamics.